The role of engineering in sustainable management of forest resources in developing countries (2018)
Forestry problems such as deforestation, degradation and biodiversity loss have persisted for years especially in developing countries, due to thr ever increasing population that depends on forest resources as a means of livelihood. Various efforts have been developed and implemented to address these problems but with little success either owing to finance or non-adaptability of available or foreign technologies being adopted. In order to improve forest conditions retention, engineers must come up with innovation , adaptation of technology to local conditions, improved working methods and processes that will not only meet the developmental need of the forest but also ensure the harmonious growth between nature, environment and forest elements. This paper focuses on several roles of engineering profession in forestry with a view to ensuring successful, healthy and safe development and sustainable management of forest resources.